Effect of Crude Aloe Vera Extract on the Histopathology of Gurame Fish (Osphronemus Gouramy) Infected with the Bacteria Edwarsiella tarda - Anarkhis, Nuranti; Prajitno, Arief; Maftuch, Maftuch (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Edwardsiella tarda is a type of gram-negative intracellular pathogen that can cause mass mortality in fish farming. The development of edwarsiellosis due to E. tarda infection causes significant economic losses for fish farmers. Aloe vera as one of the plants known to contain active ingredients that can inhibit the growth of bacteria. Aloe vera has a broad spectrum of antibacterial activity, both for inhibiting gram-positive and negative bacteria (Heng et al., 2018). The results of the toxicity test of aloe vera extract showed that when used in high doses it would cause high toxic effects, namely at a dose of 200 mg/L with mortality reaching 60% of the total tested fish. The pathogenicity of E.tarda with LD50 showed that the higher the density of bacteria, the higher the possibility that E.tarda bacteria could cause disease in its host, namely at a density of 107 it experienced 50% death. The ability of E.tarda bacteria to cause disease was also influenced by its host’s ability to fight pathogens. Based on the hispatological tests performed, there were changes in the morphology and behavior of the fish. Administration of aloe vera crude extract had an effect, namely being able to reduce the value of histopathological damage to the gills of gourami that had been infected with E.tarda bacteria with the lowest score, namely at a dose of 150 mg/L.